Empyema thoracis in an infant: A case report (Indian Journal of Child Health, 2020)
Pneumonias are often associated with pleural effusions and a small proportion of them progress to empyema. Empyema thoracis is a complication of untreated or partially treated bacterial pneumonia. It is still responsible for significant morbidity and mortality. Due to poor facilities for culture, delay in seeking medical opinion, and indiscriminate use of antibiotics, it is very difficult to isolate microorganisms. The most common organism causing empyema in infants is Staphylococcus aureus. Cases of empyema thoracis by Methicillin-resistant S. aureus (MRSA) though rare are also been reported. We hereby report a case of empyema caused by MRSA. Baby responded well following chest tube drainage along with administration of antibiotics. The present case highlights the importance of early interventions by tube thoracostomy and appropriate antibiotics for better outcome. Imaging plays an important role in the diagnosis and management of empyema.